2002
DOI: 10.1021/ja012569l
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Monolayers of Alkanethiolates on Palladium Are Good Etch Resists

Abstract: Self-assembled monolayers (SAMs) formed from alkanethiols on palladium resist corrosion by solution-phase chemical etchants, regardless of the chain length and wettability of the SAM. This insensitivity to chain length contrasts with SAMs on gold, for which a hydrophobic, well-ordered, crystalline alkane film is required to prevent access of water-soluble etchants to the underlying metal. 1,2 This paper demonstrates that dense SAMs form on contact of hexadecanethiol (C 16 SH) and palladium, and that these SAMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 8 publications
2
138
2
4
Order By: Relevance
“…Conformal, molecular/atomic-level contact between a PDMS stamp and the surface of a substrate is the key to successful transfer of ink molecules from the stamp to the substrate. µCP is widely used in printing alkanethiols on thin films of Au 10 , Ag 45 , Pd 46 and Pt 47 , and to a smaller extent (and with more difficulties) of alkylsiloxanes on silicon/silicon dioxide or glass 48 . The ink molecules form SAMs on these surfaces during the printing process.…”
Section: Fabrication Of Mastermentioning
confidence: 99%
“…Conformal, molecular/atomic-level contact between a PDMS stamp and the surface of a substrate is the key to successful transfer of ink molecules from the stamp to the substrate. µCP is widely used in printing alkanethiols on thin films of Au 10 , Ag 45 , Pd 46 and Pt 47 , and to a smaller extent (and with more difficulties) of alkylsiloxanes on silicon/silicon dioxide or glass 48 . The ink molecules form SAMs on these surfaces during the printing process.…”
Section: Fabrication Of Mastermentioning
confidence: 99%
“…The dimensions of the printed pattern are determined by the size of the raised features on the stamp: they can range from several millimeters to below 100 nm, and are typically reproduced at a 1:1 ratio. Microcontact printing (µCP) [8,11,75] has become a method of choice for patterning self-assembled monolayers (SAMs) of alkanethiols on gold [21,[76][77][78] and on other coinage metals, including silver [79,80], copper [81,82], palladium [83,84], and platinum [85]. This application takes advantage of the high affinity of the sulfur moiety for noble metals, leading to rapid adsorption of molecules under the formation of a covalent and thermodynamically stable metal-sulfur bond.…”
Section: Patterning Based On Printingmentioning
confidence: 99%
“…This resolution issue was addressed by Love et al [25] who reported that Pd substrates yielded better post-etch resolution than their Au counterparts when coated with alkanethiol monolayers for nanolithographic purposes. We have recently reported [26] that a resolution limit of ≃ 20 nm is found when 1-nonanethiol SAMs are adsorbed on sputtered Au substrates.…”
Section: B Alkanethiol Self-assembled Monolayers On Aumentioning
confidence: 99%
“…There have been numerous reports of substrate-induced effects on the quality of the patterns produced after etching in atomic nanolithography processes [25,27]. However, all such reports have apportioned blame for poor quality on either the roughness of the substrate or on the grain size.…”
Section: Alkanethiol Coverage and Dependence On Au Morphologymentioning
confidence: 99%
See 1 more Smart Citation